Passive acoustic mapping of extravasation following ultrasound-enhanced drug delivery - Paverd, C; Lyka, E; Elbes, D; Coussios, C (IOP Publishing, 2019)
The amount and distribution of chemotherapeutic agents delivered to tumours can vary significantly due to tumour heterogeneity, even under focussed ultrasound (FUS) assisted drug delivery regimes. The ability to non-invasively localise cavitation nuclei of a similar size to therapeutic drugs, both within the vasculature and tumour tissue, may provide a useful marker of ultrasound-enhanced drug delivery and extravasation. Solid polymer based nanoscale cavitation nuclei, under FUS excitation, have previously been shown to extravasate into tissue-mimicking phantoms, and to increase drug delivery in murine tumour models in vivo. Here we show in a tissue-mimicking material that these nuclei, once extravasated under FUS excitation, are still acoustically active and can be non-invasively localised using passive acoustic mapping (PAM). By using a high resolution dual linear array setup in conjunction with adaptive beamformers, we demonstrate that the average 'maximum distance' of a PAM pixel to an extravasated particle across experiments is mm. Although the primary objective of the paper is to show that extravascular cavitation can be used as evidence of successful drug extravasation in a tissue-mimicking phantom, we also recognise the physical and computational limitations of using a high resolution dual array setup with adaptive beamformers. Thus as a secondary objective, we evaluate tradeoffs between adaptive and non-adaptive beamformers, as well as between dual and single array geometries. When compared to a conventional beamformer, adaptive beamformers reduce the maximum distance of PAM pixels to extravasated particles from an average of mm to mm in the single array case. The distance is further reduced to mm using the dual array configuration, thereby demonstrating that increasing the solid angle spanned by the PAM array aperture significantly improves drug delivery localisation. Future work will test the applicability of PAM-based monitoring of ultrasound-enhanced drug delivery in vivo.